Pemanfaatan Sekam Bakar Sebagai Amandemen Tanah Dalam Budidaya Tanaman Kacang Tanah (Arachis Hypogaea L.) - Nisiyari Halawa; Aguswita Gulo; Jefon Citrawan Halawa; Karisman Putra Gulo; Yoel Melsaro Larosa (Jurnal Ilmu Pertanian dan Perikanan, 2025)
The productivity of peanut (Arachis hypogaea L.) is greatly influenced by the quality of the soil in which it is cultivated. Poor soil structure and low organic matter content are among the main limiting factors for optimal peanut growth. One potential solution is the use of rice husk charcoal (biochar) as a soil amendment. Rice husk charcoal has been shown to improve the physical and chemical properties of soil, such as enhancing porosity, cation exchange capacity (CEC), and soil pH. This study is based on a literature review of various scientific sources discussing the application of rice husk charcoal in crop cultivation, particularly legumes such as peanuts. The review indicates that rice husk charcoal can increase nutrient availability, improve soil aeration and water retention, and support root development and pod formation. Several studies also report yield increases of up to 20–30% in peanuts when appropriate doses of rice husk charcoal are applied. Therefore, rice husk charcoal can be recommended as an environmentally friendly soil amendment for sustainable peanut farming systems.